Anthelmintic Efficacy of Ethanol Extract of Raw Kepok Banana Peel (Musa paradisiaca L.) Against Ascaridia galli Worms In Vitro - Annastasya Yuliani Rahayu; Retno Sri Wahjuni; Dewa Ketut Meles; Retno Wulansari (Universitas Airlangga, 2020)
The aims of this study was to know anthelmintic efficacy through determine the concentration, duration, and interaction between concentration and duration of raw kepok banana peel ethanol extract against mortality rate of Ascaridia galli using in vitro method. Present study was used completely randomized design. This method of this study was used a total of 600 samples of Ascaridia galli with length of 7-11 cm without differentiating their sex. The concentration of raw kepok banana peel ethanol extract was divided into 25%, 50% and 75%. Physiological saline solution and piperazine citrate 10 mg/ml were being used as negative and positive control. Each treatment then being replicated six times. The recording of mortality rate was done at 2, 4, 6, 8 and 10 hours of observation. Ascaridia galli was confirmed death if there was no movement while triggered by anatomy tweezers and dipped in slightly warm water (50 0C). The data obtained was analyzed using ANOVA factorial and continued with Duncan Multiple Range Test by SPSS 26 for Windows. The results were showed that in 75% concentration and 10 hours of treatment can cause the highest mortality rate against Ascaridia galli. Interaction between concentration and duration of treatment reveals that 75% concentration of raw kepok banana peel ethanol extract in 10 hours of observation was recorded causing the highest mortality rate against Ascaridia galli.